COMPETENCE APPROACH TO FORMATION OF PROFESSIONAL AND PEDAGOGICAL CULTURE OF THE FUTURE SPECIALISTS (Pedagogy of Higher and Secondary Education, 2008)
In article problems of the competent approach in formation professionally-pedagogical culture of the future teachers are considered.